Removal of algae by sonicator: a case study from per Aru reservoir - Thurkka, T.; Mikunthan, T.; Thavaranjit, A.C.; Anoja, N. (Faculty of Agriculture, Eastern University, 2020)
Per Aru is a reservoir which rises in Vavuniya district, Northern Province, Sri Lanka with the length and basin size of 32 Km and 372 Km2 respectively. Per Aru reservoir is for the sole purpose of supplying drinking water to the urban area of Vavuniya district by National Water Supply and Drainage Board. Major problem was identified as very high algal population in the Per Aru reservoir. Hence research was focused on efficiency of ultrasound wave’s technology (Quattro- DB sonicator) to reduce the algal population in Per Aru reservoir and to evaluate the change of colour and turbidity for drinking water supply. Raw water samples were collected from April to July 2018 at monthly interval from different distance from sonicator; 50m, 100m, 150m, 200m and 500m as control in three different depths as surface, middle and bottom. EC, pH, turbidity, total hardness, nitrate, phosphate and total iron were tested. Algae population also was countered. All the parameters were within the recommended level of Sri Lankan drinking water standards except colour and turbidity. The colour (20 - 75 Pt-Co) and Turbidity (3.03 - 5.97 NTU) was very high. Efficiency of sonicator was high in the surface and algal removal percentage was ranges from 76 to 85%. Ultrasonic algal control has favourable results and sonicator efficiency was reduced with increasing distance and was reduced with increasing depth from surface to bottom. Statistical analysis shows that there were no significant variation in the efficiency in 50m and 100m distance. Algae were significantly removed in 50m, 100m than the 200m distance from the sonicator. Finally it was concluded that Per Aru reservoir has colour, turbidity and algae problem and conventional treatment is important to remove colour and turbidity. Ultrasonication has effectively control the algal population in Per Aru reservoir.
Keywords: Algae; Colour; Per Aru reservoir; Quattro-DB sonicator; Turbidity